International Perceptions of Relational Stalking: The Influence of Prior Relationship, Perpetrator Sex, Target Sex, and Participant Sex. (November 2015) - Scott, Adrian J.; Rajakaruna, Nikki; Sheridan, Lorraine; Gavin, Jeff
The present study examines the influence of prior relationship on perceptions of relational stalking in the context of both opposite- and same-sex scenarios using community samples from Australia, the United States, and the United Kingdom. The study used a quasi-experimental 3 × 2 × 2 × 2 × 3 (prior relationship × perpetrator sex × target sex × participant sex × country) independent measures design. Participants comprised 2, 160 members of the community, each receiving 1 of 12 versions of a hypothetical scenario and responding to scale items concerning the situation described. The findings support previous research, with scenarios involving a stranger (rather than an acquaintance or ex-partner), and scenarios involving a male perpetrator and a female target, being considered the most serious. The findings further indicate that female observers identify more closely with the role of the victim and male observers identify more closely with the role of the perpetrator, regardless of victim and perpetrator sex, and that differences in the findings across the three countries may be affected by location to a small but significant degree.